Effectiveness of a train-the-trainer workshop series on teaching methods among nurse educators: an exemplar from Vietnam - Van Lan Hoang; Hien Thi Bui; Thuy Thi Le; Duong Thuy Tran; Hue Thi Hoang; Hong Thuy Phuong Huynh; Thi Hoa Huyen Nguyen (Frontiers in Education)
Nurse educators play a critical role in preparing the next generation of nurses to provide high-quality patient care. The ongoing preparation of knowledge and skills for nurse educators is crucial for maintaining the quality of nursing education, particularly during the unexpected challenges such as the COVID-19 pandemic. This study aimed to examine the effectiveness of a workshop series on five concurrent teaching methods for nurse educators in Vietnam. A mixed-methods study was conducted. An online workshop series was conducted for 25 nurse educator representatives from five nursing schools across Vietnam. The workshop program covered of five teaching methods, including (i) teaching from face-to-face class to e-learning, (ii) team-based learning (TBL), (iii) case-based teaching (CBT), (iv) debriefing techniques used in simulation training, and (v) developing peer program to assist students’ learning. Pre- and post–surveys were used to test knowledge of teaching methods, followed by semi-structured individual interviews. Quantitative data were analyzed using descriptive and comparison statistics, while qualitative data underwent content analysis. Results showed a significant improvement in participants’ overall knowledge following the workshops, with the mean total score of correct answers increasing from 12.48 (SD = 2.77) in the pre-test to 16.8 (SD = 3.81) in the post-test. Substantial gains were observed in three specific areas: the classic progress of activities in team-based learning, Kolb’s experiential learning cycle in simulation debriefing techniques, and the core value of the peer mentoring model had significantly improved. Most nurse educators expressed satisfaction with the training workshops, with the “debriefing technique” being the most interesting topic. Two major themes emerged from the qualitative analysis: fostering interest in updated teaching methods and motivating the change. This study suggests that replicating the workshop series on teaching methods would be a beneficial in facilitating ongoing improvements in teaching practice in Vietnam’s nursing education system.